1996
DOI: 10.1007/bf02238954
|View full text |Cite
|
Sign up to set email alerts
|

High risk factors for rehospitalization within six months

Abstract: Global assessments and demographic information collected during an index admission can generate factors to identify patients at risk for rehospitalization within six months. History of prior admissions and non-compliance with outpatient treatment, reported as risk factors in urban settings, were found also to be risk factors in a rural region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 11 publications
1
26
0
1
Order By: Relevance
“…Our results are consistent with those who have found little association between clinical ratings and rehospitalization (Moos et al, 2000;Parker et al, 2002), employment (Moos, Nichol, & Moos, 2002), and bed days (Parker et al, 2002). However, some studies have reported an association between clinical judgment and hospitalization (Hendryx et al, 2003;Monnelly, 1997;Vetter & Koller, 1996;Walker et al, 1996), service costs (Ruggeri, Biggeri, Rucci, & Tansella, 1998), and employment (Vetter & Koller, 1996).…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Our results are consistent with those who have found little association between clinical ratings and rehospitalization (Moos et al, 2000;Parker et al, 2002), employment (Moos, Nichol, & Moos, 2002), and bed days (Parker et al, 2002). However, some studies have reported an association between clinical judgment and hospitalization (Hendryx et al, 2003;Monnelly, 1997;Vetter & Koller, 1996;Walker et al, 1996), service costs (Ruggeri, Biggeri, Rucci, & Tansella, 1998), and employment (Vetter & Koller, 1996).…”
Section: Discussionsupporting
confidence: 95%
“…This is to be expected, as it is established that characteristics such as number of previous admissions and psychiatric diagnosis are stronger predictors of readmission than levels of symptoms and functioning (Thornicroft, Gooch, & Dayson, 1992;Walker et al, 1996).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Neither the published literature nor the scale's documentation (Hodges, 1989(Hodges, , 1997 provide scale-development information about such essential tasks as item selection and weighting, determination of the domain structure, and development of the scoring methodology (Bates, 2001). Both Hodges (1997) and Bickman, Heflinger, Pion, and Behar (1992) stated that the CAFAS was adapted from an earlier scale-the North Carolina Functional Assessment Scale (NCFAS, Walker, Minor-Schork, Bloch, & Esinhart, 1996), an adult measure. In fact, 67% of items on the original CAFAS were duplicated or modified from the NCFAS (Bates, 2001).…”
Section: Description Of the Cafasmentioning
confidence: 99%
“…La NCFAS ha sido reconocida como un valioso instrumento con aplicaciones prácticas y académicas, habiendo sido usada en la evaluación de programas de visita domiciliaria con padres primerizos (De la Rosa, Perry, Dalton & Johnson, 2005; De la Rosa, Perry & Johnson, 2009), programas de prevención temprana del maltrato infantil (Fernandez, 2007), servicios intensivos de preservación familiar (Kirk & Griffith, 2007), programas de intervención culturalmente sensibles (Richardson, 2008), una intervención judicial piloto en violencia doméstica (Coll & Stewart, 2006) y en el estudio de factores de riesgo para la re-hospitalización psiquiátrica (Walker, Minor-Schork, Bloch & Esinhart, 1996). En sus distintas versiones, la NCFAS se aplica actualmente en cerca de 450 agencias y organizaciones en Estados Unidos, Canadá y Australia (NFPN, 2009).…”
Section: Antecedentesunclassified